ASP.NET MVC framework preview - Sanderson, Steven (FirstPress, 2008)
The ASP.NET MVC framework is the latest evolution of Microsoft's ASP.NET web platform. It introduces a radical high-productivity programming model, promotes cleaner code architecture, supports test-driven development, and provides powerful extensibility, combined with all the benefits of ASP.NET 3.5. ASP.NET MVC Framework Preview is a first look at this technology's main features, designed to give you a head start getting to grips with this powerful new technology.